Thermal management of water-based carbon nanotubes enclosed in a partially heated triangular cavity with heated cylindrical obstacle - Ul Haq, Rizwan; Soomro, Feroz Ahmed; Öztop, Hakan Fehmi; Mekkaoui, Toufik (Pergamon-Elsevier Science Ltd, 2019)
The aim of present article is to investigate the thermal management of water-based single wall carbon nanotubes (SWCNTs) inside the partially heated triangular cavity with heated cylindrical obstacle. In this model, thermal conductivity of liquid is comprehensively improved by introducing the SWCNT and specific conditions are introduced at the inner circular cylinder. Three various conditions (cold, heated and adiabatic) are defined at the surface of heat cylinder to maintain the thermal management. Convection in the cavity takes place due to difference between cold inclined walls and partially heated bottom wall. This phenomenon is governed by set of nonlinear partial differential equations, including continuity, momentum and energy equation. Apart from other thermophysical properties of nanofluid, effective thermal conductivity model has also been incorporated. The numerical solution is sought using Finite Element Method (FEM). The simulation is performed for the effects of cylindrical obstacles (cold, adiabatic and hot), heated lengths (A <= L-H <= 8), Rayleigh number (10(4) <= Ra <= 10(8)), nanoparticle volume fraction (0 <= phi <= 0.2), and magnetic parameter (0 <= M <= 500) on the heat transfer rate, flow velocity fields, and temperature distribution. The study concludes that at the heated length the heat transfer rate for hot cylinder is less than that of cold cylinder. Whereas, it is increased due to increase in Rayleigh number and nanoparticle volume fraction. Moreover, temperature distribution inside the cavity is increased by increasing the nanoparticles volume fraction. On the other hand, increase in magnetic field effects does not have significant impact on the temperature distribution. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: Triangular cavity; Transport phenomena; SWCNTs; Natural convection; Simulation; FEM